1969
DOI: 10.1139/p69-348
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the pigmy resonance on the calculations of the neutron capture cross section

Abstract: A comparison of the experimental cross sections of the (n, γ) reaction for several nuclei (103Rh, 127I, 181Ta, 197Au) with the compound nucleus model calculations has been made. In the formula used for the probability of gamma-ray emission from the compound nucleus, the presence of the well-known giant resonance was accounted for, as well as the presence of the "pigmy resonance" appearing at the energy Eγ ≈ 6 MeV. The agreement with the experimental values is better in this case than when the "pigmy resonance"… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
24
0

Year Published

1972
1972
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 0 publications
1
24
0
Order By: Relevance
“…Bartholomew and co-workers found an enhancement of γ -ray strength in the γ decay after thermal neutron-capture reactions in various nuclei (see, e.g., [3]). A few years later this phenomenon was denoted as "pigmy resonance" [4,5]. Nowadays, the PDR is widely accepted as a new, common mode of excitation of atomic nuclei [6].…”
Section: Introductionmentioning
confidence: 99%
“…Bartholomew and co-workers found an enhancement of γ -ray strength in the γ decay after thermal neutron-capture reactions in various nuclei (see, e.g., [3]). A few years later this phenomenon was denoted as "pigmy resonance" [4,5]. Nowadays, the PDR is widely accepted as a new, common mode of excitation of atomic nuclei [6].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is different from the traditional term "pygmy dipole resonance" which was used to refer to resonances arising from nucleons outside an N=Z core [6]. Studies in neutron-rich O, Ni and Sn isotopes [5,7,8] reported some fragmentation of the dipole strength towards lower excitation energies (E x ) that are considered to be related to the neutron skin.…”
mentioning
confidence: 99%
“…However, these are still at fairly high E x of ∼10 MeV. Dipole resonances located slightly above the neutron threshold can have impact on the neutron capture rates in r-process nucleosynthesis [6,9]. Theoretical investigations of soft dipole states in medium heavy nuclei show that the degree of collectivity is more in the isoscalar dipole operator [10,11].…”
mentioning
confidence: 99%
“…Historically, the first observation of a pygmy resonance occurred in 1961 with the discovery of a significant number of unbound states identified as a bump in γ-rays emitted following neutron capture [10]. But the first use of of the name pygmy resonance, or pygmy dipole resonance (PDR), was in 1969 when its effect on the calculations of neutron capture cross sections was reported [11]. 1 The description of the PDR as a collective excitation was first introduced in Ref.…”
Section: Origins Of the Pygmy Resonancementioning
confidence: 99%
“…where C is a kinematical constant and ψ(q) is the Fourier transform of the ground state wave function of the nucleus. In fact, this formalism works rather well for looselybound nuclei such as 11 Li and 11 Be [20,21,22]. For nucleon removal with larger separation energies, the Serber formalism is not appropriate and yields inaccurate results [22,23,24,25,26,27].…”
Section: Low Energy Response In Neutron-rich Nuclei 21 Nucleon Knockmentioning
confidence: 99%